COMMUNICATION AND SELF-CONCEPT OF CHILDREN WITH DEAF AND SPEECH IMPAIRED - Mulyadi, Eko; Oktavianisya, Nelyta; Puspaningrum, Ulva (Journal of Vocational Nursing, 2020)
Introduction: The communication and interaction is the essence of every human as a social being. But, normal communications is not realyzed by the deaf speaking children. Deaf and speech impaired children affect self-concepts that affect communication. Where it will caused them to become inferior or have less confident. The confidence is begins through the formation of self-concept which formed from the experiences in their social interactions. This study aims to find the description of the communication and self-concept of the deaf and speech impaired children in SLB Darma Wanita Sumenep. Methods: This study used qualitative as a research methode with phenomenology approach. Respondents in this study are students of SLB Darma Wanita Sumenep who deaf and speech impaired start on birth. The sampling technique is used purposive sampling counted 10 respondents.    The data collected by observation and in-depth interviews of respondents. The data were analyze with triagulation of the interview , key person, and observation. Results: Based on the results of this study, known that between the deaf speaking children and the normal people have problems in terms of understanding the symbols and sentences that there not regularly, so they often occur discommunication. The self-concept of deaf speaking children is tend to be shy with the opposite gender, less open with new people, but they have a high spirits for they futures. They need encouragement to socialize with new people and other normal people. It can make their self-concept and self-confidence can be better. Conclusion: The communication deaf and speech impaired children experience obstacles in sending or receiving messages due to interference in understanding the symbols and writing that are given.